PENERAPAN MODEL PEMBELAJARAN PROBING-PROMPTING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI IPS 1 SMAN 1 TERARA - Khairurrozi, Khairurrozi; Suryanti, Ni Made Novi; Wahidah, Ananda; Masyhuri, Masyhuri; Hamdi, Hamdi (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2023)
This is a Classroom Action Research (CAR) conducted in 2 cycles, each cycle consisting of two meetings and comprising 4 steps: (1) planning; (2) implementation; (3) observation; and (4) analysis & reflection. The research was carried out at SMAN 1 Terara, specifically in class XI IPS 1, with 36 students comprising 15 male students and 21 female students. The aim of this research is to improve students' learning outcomes in Sociology in class XI IPS 1 at SMAN 1 Terara by implementing the probing-prompting learning model. Data in this research were collected through observation, reflection, learning outcome tests, and documentation. The data analysis technique used in this research is descriptive analysis. Based on the results of the classroom action research conducted on students of class XI IPS 1 at SMAN 1 Terara, it can be concluded that the use of the Probing-Prompting learning model can improve students' learning outcomes in sociology. The improvement can be demonstrated as follows: 1) in cycle I, the implementation of the learning process was 83.3%. It then increased in cycle II to reach 100%, 2) student learning outcome data in cycle I showed mastery at 63.8%, then increased in cycle II with mastery reaching 88.8%.